A multiscale statistical method to identify potential areas of hyporheic exchange for river restoration planning - Magliozzi, Chiara; Coro, Gianpaolo; Grabowski, Robert C.; Packman, Aaron I.; Krause, Stefan (Elsevier, 2018)
The hyporheic zone (HZ) is an area of interaction between surface and ground waters present in and around river beds. Bidirectional mixing within the HZ, termed hyporheic exchange flow (HEF), plays significant roles in nutrient transport, organic matter and biogeochemical processing in rivers. The functional importance of the HZ in river ecology and hydrology suggests that river managers should consider the HZ in their planning to help compromised systems recover. However, current river restoration planning tools do not take into account the HZ. This paper describes a novel multiscale, transferable method that combines existing environmental information at different spatial scales to identify areas with potentially significant HEF for use in restoration prioritization and planning. It uses a deductive approach that is suited for data-poor case studies, which is common for most rivers, given the very limited data on the spatial occurrence of areas of hyporheic exchange. Results on nine contrasting European rivers, demonstrate its potential to inform river management.
Keywords: Hyporheic zone; Statistics; Hyporheic exchange flow; Cluster analysis; Catchment management; River basin management